The child and the spirit: Archetypal patterns in New Woman fiction. - Mei-Fang Chang (2007)
This thesis offers a Jungian-inflected reading of three key New Woman novels: Mona Caird's The Daughters of Danaus (1894), Sarah Grand's The Beth Book (1897), and Olive Schreiner's From Man to Man (1926). By examining two archetypal images---the Child and the Spirit---not as psychological entities but as symbolic forms in the socio-cultural context of the fin de siecle, I explore the ways in which feminist New Woman writers seek to present women artists' collective experience and the extent to which their work revises the dominant discourses of female subjection and sacrifice. Part I is engaged with the Child Archetype with a focus first on the Abandoned Child, where I investigate sisterless children through a combined discourse of sisterhood and trickster. In Chapter 1, I add a discussion of Caird's maternal theory and a mythic reading to examine motherless children. In Chapter 2, I include a study of a loverless child to cast light on the conventional ideology of woman's purity. In the second section of this Part, where Chapter 3 is located, I scrutinize the ways in which Grand portrays the Nature Child in the Romantic and Transcendental fashions, the ethics of which, I argue, anticipate today's ecofeminism. Part II deals with the Spirit Archetype in different manifestations (the Wise Old Man in Chapter 4, the Romantic Knight in Chapter 5, and the Platonic Lover in Chapter 6), drawing attention to gender-power politics in relation to the New Man and the New Woman by adopting different approaches (revised Jungian, quasi-Bakhtinian Camivalesque, and narratology). Shifting signifiers, the Child and the Spirit archetypes, I argue, are New Woman writers' strategic vehicles to (con)textualize women's collective concerns. This act of female "unconsciousness-raising" caused a sensation at the time and can now serve to better our understanding of the diversity and discursiveness of the New Woman movement.